Complexity and complication in dynamics of linear spatial socio-economies, a synopsis - Michael Sonis (European Regional Science Association (ERSA), 2002)
The purpose of this study is to provide an explanation of the process of complication, i.e., the deepening of complexity in evolving complex linear systems. The complication means the transfer from complex structure to much more complex structure in the evolution of complex system. The paradigm of complication pointed out on the deficiency of purely economic considerations of socio-economic systems and stresses the necessity to widen the concept of "Homo Oeconomicus" to the concept of "Homo Socialis". Such a widening is radical in the study of complex socio-economic processes because of the important difference between economic and socio-economic rationality: the traditional identification of economic rationality of "Homo Oeconomicus" as optimization is complementary to socio-economic rationality of "Homo Socialis" as parsimonity. In our paper we will apply the paradigm of complication to the several main branches of Spatial Analysis connected with the augmentation and development of flows, networks and superposition of their hierarchies in linear systems. We are using the concept of complication as the unifying frame for theories of linear spatial analysis of complex socio-economic systems: the Push-Pull theory of migration streams, the theory of Central place hierarchies, the spatial production cycles and trade feedback loops, the Dynamic Input-Output analysis and the modern theory of the Fields of Influence of chandes in Input-Output systems, the classical Key Sector analysis, the structural Q-analysis and the Miyazawa model of income distribution within Input-Output systems and their "onion skins" extensions.
Keywords: 330